Oil bioremediation in the marine environment of Antarctica: a review and bibliometric keyword cluster analysis - Zakaria, Nur Nadhirah; Convey, Peter; Gomez-Fuentes, Claudio; Zulkharnain, Azham; Sabri, Suriana; Shaharuddin, Noor Azmi; Ahmad, Siti Aqlima (MDPI, 2021)
Bioremediation of hydrocarbons has received much attention in recent decades, particularly relating to fuel and other oils. While of great relevance globally, there has recently been increasing interest in hydrocarbon bioremediation in the marine environments of Antarctica. To provide an objective assessment of the research interest in this field we used VOSviewer software to analyze publication data obtained from the ScienceDirect database covering the period 1970 to the present, but with a primary focus on the years 2000–2020. A bibliometric analysis of the database allowed identification of the co-occurrence of keywords. There was an increasing trend over time for publications relating to oil bioremediation in maritime Antarctica, including both studies on marine bioremediation and of the metabolic pathways of hydrocarbon degradation. Studies of marine anaerobic degradation remain under-represented compared to those of aerobic degradation. Emerging keywords in recent years included bioprospecting, metagenomic, bioindicator, and giving insight into changing research foci, such as increasing attention to microbial diversity. The study of microbial genomes using metagenomic approaches or whole genome studies is increasing rapidly and is likely to drive emerging fields in future, including rapid expansion of bioprospecting in diverse fields of biotechnology.